Production of homogeneous particleboard from residual oversize fibers of a MDF industry Produção de painéis aglomerados homogêneos a partir de fibras oversize residuais de uma indústria de MDF - Franca M.C.* (2016)
The objective of this study was to evaluate the technical feasibility of production of particleboard from oversize fibers taken from the MDF production process. The raw material used was composed of flake particles, a MDP company, and resin-coated fibers removed before the formation of the mattress of MDF panels, both formed by the mix of Pinus taeda and Pinus elliottii. The experiment involved 5 homogeneous treatments in proportions of 100 parts of particulate 0 shares fibers, 75:25, 50:50, 25:75, 0: 100. Please note that each composition was manufactured with 12% urea formaldehyde resin and 1% paraffin emulsion. Assays were developed in accordance with ASTM (1993), DIN (1982) and ABNT (2006). In the analysis of the results the analysis of variance and the Scott-Knott test at 95% probability was applied. As a result a positive influence of the use of oversize fibers in technological properties of the panels was found. The best study treatments were composed of 75% to 100% oversize fibers.